PENGARUH PENAMBAHAN KOLANG-KALING TERHADAP KUALITAS NUGGET - Ningsih, Tuti Ayu; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was motivated on the use of fleas in food processed are not yet varied. The fleas contains crude fiber and high carbohydrates that are useful for the body and health. This study aims to analyze the effect of quality of fleas using 5%; 10%; And 15% on Nugget quality in terms of shape, color, flavour, texture and taste. This type of research is purely experimental with a completely randomized design method. The data used are primary data sourced from 30 semi-trained panelists by submitting the organoleptic test format. Analyze data using ANAVA, if Fcount> Ftable then proceed with Duncan test. The results showed that there was a significant effect on the addition of fleas as much as 5%, 10%, 15% to the quality of flavour, texture and nugget taste, while for the quality of shapes, colors, and hedonic tests there was no significant difference Because Fh <Ft.Keyword: Kolang-kaling, Nugget, Organoleptic Test.